The global value chains and the evolution of chinese economic model - Ilhéu, Fernanda (2020)
According to the Word Bank in the first 38 years of China Economic Reform took 700 million people out poverty line in China at same time benefiting the Global South economy due to the integration of the Transnational Enterprises Global Value Chains with China. Chinese government understood the economic rational of Global Value Chains, Flying Geese Model and Foreign Direct Investment Theories and introduced policies to attract foreign capital, technology, production, and foreign buyers, placing China as the final stage of the production networks in Asia and also transforming China in the biggest buying market of many resources and energy suppliers from less developed countries in Asia, Africa and South America. But a new model of Chinese economic development even more interconnected and interdependent with the world is now on move. Even quite before the world acknowledge the protectionist mindset of the US in Trump era, Chinese President Xi Jinping launched in 2013 a very ambitious initiative under the name of “One Road One Belt the 21st-Century Maritime Silk Road” to enhance a new stage of world globalization, which together with two complimentary initiatives the “International Production Cooperation” and “Third-country Market Cooperation” and in complementarity with the “Made in China 2025” and “Internet Plus” plans will lead China to develop Global Value Chains leaded by Chinese companies and integrating countries of Europe, Africa, Asia, and South America.